Adulthood consequences of spinal deformity surgeries in neurofibromatosis type 1 patients - Arihiko Tsukamoto; Koki Uno; Teppei Suzuki; Masaaki Ito; Keita Nakashima; Kenichiro Kakutani; Yoshiki Takeoka (BMC Musculoskeletal Disorders)
Abstract Background Spinal deformity associated with Neurofibromatosis type1(NF-1) is known to be intractable, and it’s surgical outcome is known to be poor. However, it is not clear whether or not patients are able to lead a healthy social life as adults, and we investigated the surgical outcomes of patients who had reached adulthood after surgery. Methods Thirty-eight patients (16 males, 22 females) who had undergone spinal deformity surgery and had reached the age of 18 years at last follow up were included. X-rays, surgery, complications, survival rate, employment status, and married rate were evaluated. HR-QOL was compared with those of adolescent idiopathic scoliosis(AIS) operated in our hospital. The idiopathic scoliosis group includes 110 patients who had undergone surgery from 2015 to 2018 at our hospital and 38 patients(2 males, 36 females) were selected by excluding patients who could not be followed up until the age of 18 years and those who did not describe their HR-QOL, and adjusting the mean preoperative cobb angle values to match those of the NF-1 group. Results The mean age at the initial surgery was 14.6 [4〜49] years, and the mean age at the last observation was 29.4 [18〜56] years. Anterior and posterior fusion were performed in 18 patients, posterior fixation was performed in 20 patients. Five patients died (3: malignant schwannoma, 1:brain tumor, 1:unknown), with a mean age of 27.0 [18〜35] years at the time of death and 12.2 [3〜21] years after the last surgery. Two patients over 40 years of age were treated for vascular system disorders, and 1 patient for a brain tumor. All survivors were ambulators except 1 case of non-ambulator due to neoplastic destruction of the hip joint. The working status was light work in 13 patients, desk work in 7, unemployed in 4, students in 8. Four patients were married. SRS-22 and ODI at the last follow-up in the NF-1 group and AIS group were compared. There were no significant differences in SRS-22 Pain, Mental Health, Satisfaction, and ODI, but SRS-22 Function and Self-image were significantly lower in the NF-1 group. Conclusions At an average follow-up of 14.8 years after surgery, 5 of 38 patients had died, 29 patients (76.3%) were able to lead a social life. However, HR-QOL was lower than that of AIS. Patients undergoing NF-1 scoliosis surgery require careful long-term follow-up, taking into account the possibility of reoperation due to osteolysis, malignant changes in the tumor, and vascular problems due to vascular fragility